2014
DOI: 10.1055/s-0034-1389373
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Anatomical Study of Tailored Far-Lateral Approach for the VA-PICA Regions

Abstract: Objective The extent of the far-lateral approach (FLA) has not yet been quantified for the region of the vertebral and posterior inferior cerebellar arteries (VA-PICA). We quantitatively analyzed six main sequential steps of the FLA. Methods A modified small FLA (msFLA) and a classic large FLA (clFLA) were performed sequentially on both sides of five cadaveric heads. A frameless navigational system was used to quantify the angle of attack for the origin (T1) and lateral medullary segment (T2) of the PICA and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
(58 reference statements)
0
3
0
8
Order By: Relevance
“…5,14,19,31 Keyhole and endoscopic subtemporal ap- proaches, as well as zygomatic arch osteotomy, have been proposed to reduce these complications. 3,15,17,18 The term "keyhole surgery" does not refer to a specific technique or approach but rather to a philosophy that emphasizes using the smallest opening necessary to achieve the anatomical goals of surgery. 9,21,25 Ideally, the aim of any neurosurgical procedure used to access deep brain lesions should be minimal brain retraction.…”
Section: Discussionmentioning
confidence: 99%
“…5,14,19,31 Keyhole and endoscopic subtemporal ap- proaches, as well as zygomatic arch osteotomy, have been proposed to reduce these complications. 3,15,17,18 The term "keyhole surgery" does not refer to a specific technique or approach but rather to a philosophy that emphasizes using the smallest opening necessary to achieve the anatomical goals of surgery. 9,21,25 Ideally, the aim of any neurosurgical procedure used to access deep brain lesions should be minimal brain retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Principles in Direct Surgery for VAFA D'Ambrosio et al reported that for approaching the VA-PICA region while minimizing the risk of LCN palsy, a trajectory from the caudo-dorsal side of the vulnerable LCNs should be used, and that the next most useful corridor is the space between the LCNs and 7-8th nerve complex (35)(36)(37). To use these two corridors from a more caudo-dorsal direction, we utilize the suboccipital far lateral approach.…”
Section: Treatment Selectionmentioning
confidence: 99%
“…São eles o acesso transfacetário, o retrocondilar, o transcondilar parcial, o transcondilar total, o acesso transjugular extremo lateral e o acesso transtubercular 13 . Importante salientar que, atualmente, a condilectomia não é passo obrigatório do acesso extremo lateral, devendo a craniotomia ser centrada na fossa subcondilar 10,[37][38][39][40] .…”
Section: 2unclassified
“…A necessidade e o benefício da condilectomia do terço posterior do côndilo variam de acordo com o tamanho do côndilo occipital, com a forma e o tamanho do forame magno, com a distância entre a porção rostral/ventral do tronco cerebral em relação ao clivus, com a quantidade de drenagem liquórica da cisterna magna e o grau de relaxamento cerebral, com o tamanho do desvio do tronco cerebral e dos nervos cranianos pela afecção específica da transição occipitocervical, com o trajeto da artéria vertebral através da dura-máter, com a altura da confluência das artérias vertebrais para a formação da artéria basilar, com as variações anatômicas da artéria cerebelar posteroinferior e com o tamanho do tubérculo jugular [37][38][39][40] .…”
Section: 2unclassified
See 1 more Smart Citation